Caregiver perceptions of care of a medical-dental community clinic for adults with autism and intellectual disabilities: Implementing a program evaluation. Issue 4 (2nd October 2021) - Lai, Jonathan; Luo, Owen Dan; Klag, Malvina; Shikako-Thomas, Keiko
ABSTRACT: Background: Providing medical and dental care for adults with developmental disabilities requires specialised care that includes caregiver's perceptions of processes of care as integral to informing care delivery. Method: We examined the reach and efficacy of a medical-dental clinic serving adults with developmental disabilities as part of a program evaluation in the community setting. Using the RE-AIM framework, we analysed caregivers' perceptions of the processes of care and associations with sociodemographic factors and stress and depression levels. Results: Perceptions of the processes of care were correlated with caregiver stress levels. Low satisfaction with receipt of general and specific information suggests that care coordination should be prioritised. Conclusions: The ecosystem of care needs to be targeted in addition to services directed at the individual. Shared evaluation frameworks between service deliveries modalities would allow comparison of family-centred care delivery systems.